(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The landscape of historical areas holds significant cultural, aesthetic, and environmental value, reflecting the heritage and identity of communities. Modern approaches to improving and developing these landscapes focus on balancing preservation with sustainable innovation. This study explores contemporary strategies and techniques aimed at enhancing the ecological, social, and visual qualities of historical sites without compromising their authenticity. Key directions include the integration of green infrastructure, use of native plant species, adaptive reuse of open spaces, and incorporation of community participation in planning processes. The findings highlight that a multidisciplinary approach combining heritage conservation, landscape architecture, and environmental management can effectively revitalize historical landscapes, ensuring their resilience and relevance for future generations.